ОПРЕДЕЛЕНИЕ СТЕПЕНИ НАКОПЛЕННОЙ ДЕФОРМАЦИИ В ЭЛЕМЕНТАХ ЖЕЛЕЗНОДОРОЖНОГО КОЛЕСА Ø 927 ММ (Modern Problems of Metallurgy, 2020)
In the process of hot plastic deformation features of the metal flow and degree of deformation of the metal of elements of the railway wheel diameter 927 mm with C-shaped disc have been defined and studied.
Keywords: continuous cast billet, all-rolled wheel, degree of deformation, density of dendritic structure